PERSEPSI PENGUNJUNG TERHADAP PRODUK DI PASAR WISATA PASAR BAWAH PEKANBARU - Hilda Sari Wardhani; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
research purposed to get known about (1) how the tourists perception of Pasar Wisata Pasar Bawah in Pekanbaru include variabels of price, packaging, quality (2) effort markeeter to optimize the availability of souvenir products at market tourism Pasar Bawah Pekanbaru city. This research used quantitatif desciptive method to analyze the problems. Samples on this research are 100 samples. Whereas data collection techniques took by observation, questionnaire, and documentation. And data analysis technique used interval distribution method is grouping data into several categories. The result of this research are the dominant is the female visitors with the age range 26-45 years, from other regions in riau Province with income> 3.000.000 and have job of private employee / entrepreneur and the perception of visitors who buy souvenir products at market tourism Pasar Bawah is quite satisfied on the price, packaging of products and the quality. And visitors assess the product souvenir is good.Keywords : Tourist Perception, Product, Shopping Tourism.